Elements development on horizontal bar in men's artistic gymnastics in japan literature - Nakasone, M. (Science of Gymnastics Journal, 2015)
More recently a total of 800 elements have been recorded in the Gymnastics Code of Points. However few of theses elements made gymnastics history. As such we wonder by whom, when or where these various elements are performed. The purpose of this study was to collate data elements on the Horizontal Bar (HB) in men`s artistic gymnastics and to suggest new elements in the future. The method of study was undertaken by bibliographic analysis. This article refers mainly to journals that were published by the Japan Gymnastic Association, and a list that was made regarding the occurrence of new elements on HB in Men`s artistic gymnastics. From the analysis, the author gatherd data regarding various elememts that were performed. For example, Swing forward and vault backward straddle to hang (Tkatchev) was performed by Tkatchev A. in the 1979 World cup. A Tkatchev stretch was performed by Liukin V. and Nishikawa D. in the 1988 Seoul Olympics. In conclusion, developments of HB elements are greatly influenced by the improvement of apparatus, rules of the era. In the near future, directions of new occurring elements on the HB may add twists to the existing elements.